Energy change and space motion of electron in sinusoidal field with random phase jumps or elastic collisions - Ostroushko, V. (Вопросы атомной науки и техники, 2015)
Two different types of electron motion are considered: the one-dimensional motion in the electric field, which time dependence differs from sinusoidal one through instant jumps of phase, and the three-dimensional motion in the sinusoidal field interrupted with elastic collisions. The dependencies of the characteristic electron energy and of the characteristic dimensions of the space required for electron motion on the number of phase jumps or elastic collisions are obtained. Розглянуто два різних типи руху електрона: одновимірний рух у електричному полі, залежність якого від часу відрізняється від синусоїдальної через миттєві стрибки фази, та тривимірний рух у синусоїдальному полі, який переривається пружними зіткненнями. Отримано залежності характерної енергії електрона та характерних розмірів простору, потрібного для руху електрона, від кількості стрибків фази або пружних зіткнень. Рассмотрено два разных типа движения электрона: одномерное движение в электрическом поле, зависимость которого от времени отличается от синусоидальной мгновенными скачками фазы, и трехмерное движение в синусоидальном поле, прерываемое упругими столкновениями. Получены зависимости характерной энергии электрона и характерных размеров пространства, требуемого для движения электрона, от количества скачков фазы либо упругих столкновений.